Hiper-ideais de operadores entre espaços de Banach - Santos, Djair Paulino dos (2017)
In the present work we investigate topics of the theory of multi-ideals and hyperideals, introduced by Botelho and Torres. We also investigate the connection between the concept of hyper-ideals and the notion of coherence of multi-ideals.